Adaptive building roof combining variable transparency shape-stabilized phase change material: Application potential and adaptability in different climate zones. (15th August 2022) - Wang, Pengcheng; Liu, Zhongbing; Zhang, Xiaoyang; Zhang, Hangming; Chen, Xi; Zhang, Ling
Abstract: The development of adaptive building envelopes to achieve building energy efficiency is significant for reducing carbon emissions. This study proposed an adaptive building roof by utilizing the variable transparency characteristics of shape-stabilized phase change material. The envelope can regulate solar absorptivity in response to changes in ambient temperature to reduce unexpected heat gain or heat loss. A mathematical model was developed and verified by experiments. On this basis, the impacts of key parameters, including the melting temperature, thickness, extinction coefficient of phase change material, and the reflectivity of reflective film, on the envelope performance were investigated. Finally, the typical daily, seasonal and annual dynamic performance was compared between the new roof and the common insulation roof in different climate zones. The results show that the optimal melting temperature and thickness of the phase change material are 24 °C and 8 mm in Beijing, 24 °C and 4 mm in Changsha and Guangzhou, and 21 °C and 5 mm in Urumqi. In the four cities, the optimal extinction coefficients of the phase change material in the transparent/opaque state are 10 m −1 and 250m −1 and the optimal reflectivity of reflective film is 0.95. In Beijing, Changsha, Guangzhou, and Urumqi, the cumulative annual loads are 55 kWh/m 2, 42 kWh/m 2, 22 kWh/m 2, and 85 kWh/m 2, respectively. The corresponding energy-saving rates are 14.06%, 17.65%, 31.25%, and 9.57%. The new roof has better performance in Cwa and Cfa climate areas. This study provides theoretical guidance for the application and optimization of the new roof in different climatic regions. Highlights: A numerical model of adaptive building roof (ABR) was built and verified by experiments. The impact of key parameters on the performance of ABR was investigated and optimized. The energy performance was compared between ABR and a common insulation roof. The annual load of ABR was reduced by 9.57%–31.25% in the four studied cities.